FROM TEXTUAL TO CONTEXTUAL: CONTEMPORARY ISLAMIC THINKER ABDULLAH SAEED ON QUR’ANIC EXEGESIS - Nuraini, Nuraini; Waharjani, Waharjani; Jailani, Mohammad (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2024)
The Qur’anic tafsir (exegesis) has undergone changes over time, addressing issues from classical eras to current challenges faced by the Muslim community. Concerns have been raised about approaches that are overly literal or forceful in understanding the contexts of Qur’anic verses for application in the present time. Hence, there is a need to formulate a more profound effort to explore the meanings of the Qur’an to extract its messages and guidance. This involves understanding the contextual aspects of Qur’anic verses in terms of history and literal meanings, applying them to contemporary situations. However, as highlighted, there appears to be a gap between existing theories and their practical realities. This underscores the necessity for more careful and structured research to bridge the theoretical and practical aspects. The objective of this study is to analyze the contextualization of the Qur’an in the contemporary era, as pioneered by Abdullah Saeed. The study employed a qualitative method with an analytical study approach, utilizing literature review as the primary data collection method, drawing from Abdullah Saeed’s writings, journal articles, books, and relevant references. The findings revealed that Abdullah Saeed’s contextualization of the Qur’an is highly relevant in understanding verses that remain textual and challenging to interpret. With the evolution of the modern era, there is a need for reinterpretation, especially in the context of nation-building and culture. The local descent of Qur’anic revelations and the complexity of developments in the modern context necessitate a new understanding. The understanding sought in the current context is dynamic and can contribute to a more harmonious life. This points towards a new direction for humanity in the current millennial era.